The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1403397
|View full text |Cite
|
Sign up to set email alerts
|

Blood velocity measurements using laser speckle imaging

Abstract: Blood velocity measurements in the skin of pigs are reported. Measurements were obtained using laser speckle contrast analysis with a multiple scattering correction. Laser speckle contrast analysis is a rapid technique for obtaining a velocity mapping of perfused tissue. Measurements of blood velocity in pig skin were obtained using a laser and a monochrome digital camera. Blood velocities were measured in tissue prior to and after elevation of flaps. The effect of Iloprost and nitroglycerine on local blood ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…where α is a conversion factor that correlates SFI( i , j ) with the CBF( i , j ), which equals the slope of the linear regression line obtained from the flow phantom experiment (see Supplementary Note 1 ). In previous studies and based on our flow phantom experiment, the results of the LSCI measurement revealed a high correlation and were consistent with flow index ( K 2 ) and absolute flow velocity ( Winchester and Chou, 2004 ; Ambrus et al, 2016 ). Moreover, according to Eq.…”
Section: Methodssupporting
confidence: 87%
“…where α is a conversion factor that correlates SFI( i , j ) with the CBF( i , j ), which equals the slope of the linear regression line obtained from the flow phantom experiment (see Supplementary Note 1 ). In previous studies and based on our flow phantom experiment, the results of the LSCI measurement revealed a high correlation and were consistent with flow index ( K 2 ) and absolute flow velocity ( Winchester and Chou, 2004 ; Ambrus et al, 2016 ). Moreover, according to Eq.…”
Section: Methodssupporting
confidence: 87%
“…ml/s), and the results are expressed as flux measured in arbitrary laser speckle perfusion units (LSPU). Studies using a flow phantom have been performed to validate the technique [10,11]. The phantom consisted of a single tube embedded in a tissue-like substrate to resemble a single blood vessel, and an infusion pump was used to power the actual flow of blood or of solutions with artificial particles.…”
Section: Introductionmentioning
confidence: 99%
“…The use of milk has a number of advantages over the use of blood; specifically, it does not sediment, it is much easier to handle, and presents a behavior similar to intralipid solutions (Waterworth et al 1995, Cubeddu et al 1997. This fluid has also been used in several optical based studies (Wojtkiewicz et al 2009, Figueiras et al 2010, Figueiras 2012, and in some LSCI works (Winchester andChou 2004, Thompson andAndrews 2010). The work from Thompson and Andrews (2010) applied a multi-exposure LSCI to milk, with results similar to those found in red blood cells.…”
Section: Phantommentioning
confidence: 99%